Finite element analysis of fire-damaged flexible pavement deterioration. (12th June 2017) - van Staden, Rudi; Fragomeni, Sam
Abstract : Purpose: This research aims to use the finite element method to examine critical distress modes in the pavement layers due to changes in the structural properties brought upon by fire damage. Design/methodology/approach: A full dynamic analysis is performed to replicate heavy vehicle axle wheel loads travelling over a pavement section. Findings: Results show a 72 per cent decrease in the number of load repetitions which a fire-damaged pavement can experience before fatigue cracking of the asphalt. Further, there is a 51 per cent decrease in loading cycles of the subgrade before rutting of the fire-damaged system. Originality/value: Fatigue of asphalt and deformation of subgrade from repeated vehicular loading are the most common failure mechanisms, and major attributors to pavement maintenance and rehabilitation costs. Pavement analysis has always been concentrated on evaluating deterioration under regularly occurring operational conditions. However, the impact of one-off events, such as vehicle petroleum fires, has not been evaluated for the effects on deterioration.